Reviving the spiritual roots of agriculture for sustainability in farming and food systems: Lessons learned from peasant farming of Uttarakhand Hills in North-western India - Bisht, Ishwari Singh; Rana, Jai Chand (Science and Education Publishing Co., Ltd., 2020)
The modern industrial agriculture is in crisis. People are questioning the quality, safety and sustainability of our industrial food system. People are also questioning the wisdom of scientific agriculture as science has eventually succeeded in taking the sacred out of farming. However, the crisis brings with it opportunities for decisive, positive change. Based on our recent studies on agri-food system dynamics of traditional small-scale hill farming in Uttarakhand state of north-western India, we could document some community LEK-based innovations that can bring sustainability in food and farming systems. The lessons learned are presented here in this communication that are expected to help create a regenerative farming system mainly by reclaiming the spiritual roots of farming and food systems.